Molecular docking study of Xanthyl Chalcone derivatives as potential inhibitor agents against KIT tyrosine kinase and KIT kinase domain mutant D816H - Muthia Rahayu Iresha, Jumina Jumina, Harno Dwi Pranowo (Journal of Applied Pharmaceutical Science, 2020)
The mutation of D816H that occurs in the tyrosine kinase protein is responsible for gastrointestinal stromal tumors (GISTs). The mutation is commonly followed by the formation of a protein-resistant expression, thus new inhibitor agents are highly required in the near future. Molecular docking studies were carried out to evaluate the inhibition activity of six xanthyl chalcone derivatives to the wild and mutant types of KIT tyrosine kinase protein. The results showed that six xanthyl chalcone derivatives gave strong binding interactions with both tyrosine kinase proteins yielding on binding energy of −8.45 to −11.8 kcal mol−1, respectively. The molecular docking studies confirm that the binding interactions between the xanthyl chalcone and the amino acid residue were similar to those of sunitinib as the native ligand. Among all xanthyl chalcone derivatives, compound X6 possessed the lowest free binding energy value. Thus, compound X6 possibly has the highest inhibition activity toward wildtype and D816H mutant KIT protein. X6 was observed successfully to bind the activated KIT tyrosine kinase active site with a low binding energy value of −11.22 kcal mol−1. Therefore, this compound could become a promising inhibition agent to treat GISTs.
Keywords: Molecular docking, gastrointestinal stromal tumors, KIT kinase domain, KIT kinase domain mutant D816H, xanthyl chalcone.